Determination of University Students’ Preventive Attitudes for Lung Cancer and Healthy Life Awareness and The Influencing Factors - Melike Demir Doğan (Genel Tıp Dergisi)

(untitled)
Aims: The purpose of this study was to determine university students' attitudes toward lung cancer screening and healthy lifestyle and the factors that influence these attitudes.Methods: In the study, the data were collected from 295 students between September 2022 and February 2023 by using a personal information form, the Healthy Life Awareness Scale (HLAS), the Health Belief Model Scale for Lung Cancer and Screening (HBMSLCS).Results: It was observed that the sensitivity perception and barrier perception subscales of the HBMSLCS were higher in men than their female counter parts, and those with extended families had higher severity perception and barrier perception than those with nuclear families. As the general health status improved, the sensitivity perception and the severity perception decreased. Sensitivity perception was higher in smokers than in non-smokers. Non-smokers had higher health motivation than non-smokers. Moreover, the barrier perception was higher in those consuming alcohol compared to those who did not. As the HLAS increased, it was observed that the severity perception and barrier perception subscales of the HBMSLCS decreased.Conclusion: Consequently, it was determined that the students perceived lung cancer screening as beneficial, but they were not sensitive enough to have screening. The barrier perception related to screening was low, the health motivation was high, and the severity perception was moderate.